PEMBAGIAN WARIS ADAT MASYARAKAT SUKU BUGIS DI KECAMATAN ENOK, KABUPATEN INDRAGIRI HILIR, PROVINSI RIAU - DEO ANDIKA PUTRA SIHOMBING (PREMISE LAW JURNAL, 2017)
Bugis tribe is one of the four tribes in South Sulawesi. In the case of inheritance, Bugis tribe recognizes parental kinship system. Bugis people who reside in Enok Subdistrict have their own custom and adat law which have come from generation to generation. The research problems were as follows: how about the inheritance distribution, the types of dispute in inheritance, and the settlement of dispute in inheritance in Bugis community in Enok Subdistrict. The research used judicial empirical method in which law is conceived as a real social structure related to the other social variables. The result of the research shows that the distribution of inheritance in the Bugis community is done in three ways: hibah of gift, wasiat or last will and testament, and after a testator dies. The inheritance dispute in Enok Subdistrict is about the choice of the inheritance system by the family; it is not mpossible for females to get more portion than males. They still tend to settle their problems by Family Negotiation where the distribution of inheritance is negotiated among family members. Usually, the oldest son or uncle is appointed as the mediator. If negotiation fails, it is brought to an adat leader to help them settle the dispute. Keywords: Distribution, Adat Inheritance, Bugis Tribe